Submassive Pulmonary Thromboembolism in a Patient with Thrombocytopenia: Therapeutic Challenge - Ronni Andrea Muñoz Tovar; Luis Carlos Alvarez Perdomo; Sandra Milena Rojas Molina; Silvana Jimenez Salazar (Case Reports in Critical Care)
Venous thromboembolic disease is an important cause of mortality worldwide. A widely recognized risk factor is active neoplasia, mainly hematological tumors, in which associated thrombocytopenia can be a frequent complication. We present the case of a patient with submassive pulmonary thromboembolism associated with severe thrombocytopenia with signs of right heart failure and a requirement for systemic thrombolysis and anticoagulation, however with absolute contraindication for them. The case establishes a therapeutic challenge for the treating group, leading us to carry out an extensive search of the literature and propose a management algorithm in this complex situation.